Sustainable land management: lessons from the East African Highlands - Pender, John L.; Place, Frank; Ehui, Simeon (International Food Policy Research Institute, 2006)
As population density increases and agriculture intensifies in Africa in the future, policymakers, development practitioners, and farmers may find useful lessons in the experiences of the East African high-lands. The highlands of Ethiopia, Kenya, and Uganda face complex problems of severe poverty, low productivity, and poor natural resource management. These highlands contain some of the most densely populated areas in all of Africa.